New sight of herding behavioural through trading volume - Nizar Hachicha (Kiel Institute for the World Economy (IfW), 2010)
In this study, we employ an innovative new methodology inspired from the approach of Hwang and Salmon (2004) and based on the cross sectional dispersion of trading volume to examine the herding behavior on Toronto stock exchange. Our findings show that the herd phenomenon consists of three essential components: stationary herding which signals the existence of the phenomenon whatever the market conditions, intentional herding relative to the anticipations of the investors concerning the totality of assets, and the third component highlights that the current herding depends on the previous one which is the feedback herding.
Keywords: D53; G12; C13; 330; Herding behavior; market return; trading volume